A Green Process for High-Concentration Ethylene and Hydrogen Production from Methane in a Plasma-Followed-by-Catalyst Reactor - 王康军 李小松 朱爱民 (Plasma science & technology, 2011)
A green process for the oxygen-free conversion of methane to high-concentration ethylene and hydrogen in a plasma-followed-by-catalyst （PFC） reactor is presented. Without any catalysts and with pure methane used as the feed gas, a stable kilohertz spark discharge leads to an acetylene yield of 64.1%, ethylene yield of 2.5% and hydrogen yield of 59.0% with 80.0% of methane conversion at a methane flow rate of 50 cm^3/min and a specific input energy of 38.4 kJ/L. In the effluent gas from a stable kilohertz spark discharge reactor, the concentrations of acetylene, ethylene and hydrogen were 18.1%, 0.7% and 66.9%, respectively. When catalysts Pd-Ag/SiO2 were employed in the second stage with discharge conditions same as in the case of plasma alone, the PFC reactor provides an ethylene yield of 52.1% and hydrogen yield of 43.4%. The concentrations of ethylene and hydrogen in the effluent gas from the PFC reactor were found to be as high as 17.1% and 62.6%, respectively. Moreover, no acetylene was detected in the effluent gas. This means that a high concentration of ethylene and oxygen-free hydrogen can be co-produced directly from methane in the PFC reactor.